The Power of Trust: Exploring the Mediating Role of Brand trust on Influencer credibility and Product quality's Impact on Avoskin Purchase Intention at Dian Nuswantoro University - Navarida, Feby Nasywa; Setiawan, Aries; Damar, Haunan; Wibowo, Mochammad Eric Suryakencana (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the mediating role of brand trust in the relationship between influencer credibility, product quality, and purchase intention for Avoskin products. Using PLS-SEM, data were obtained from 180 students at Universitas Dian Nuswantoro. Product quality and brand trust show positive, significant effects on purchase intention, whereas influencer credibility shows no direct effect. Influencer credibility and product quality significantly enhance brand trust, which in turn mediates their effects on purchase intention. The findings underscore the strategic importance of product quality in building brand trust and increasing consumers’ purchase intentions.